Impact of COVID-19 on physical activity patterns in non-professional populations in Asia: a mini review of pre-, during, and post-pandemic periods - Jiang, Zonglin; Zhou, Qianhui; Shu, Haolu; Jiang, Linjing (Frontiers in Public Health, 2025)
This mini-narrative review examines the impact of the COVID-19 pandemic on physical activity (PA) patterns across Asian countries, including regions such as Hong Kong, South Korea, Japan, and Southeast Asia. Pre-pandemic (before 2019), Asia experienced gradually increasing PA participation rates, characterized predominantly by outdoor activities, gym workouts, and organized group exercises, driven by growing fitness awareness and the availability of facilities for exercise. During the pandemic (2020–2022), widespread declines in regular exercise occurred due to restrictions, causing a substantial shift toward indoor, home-based, and online-based PA. Low PA adversely affects cardiovascular health, immune function, obesity, metabolic conditions, and psychological well-being. Although home-based exercise modalities partially mitigated these impacts, their effectiveness remained limited compared to pre-pandemic routines. In the post-pandemic period (2022–2025), PA in Asia partially recovered, with some regions, such as Hong Kong and South Korea, reporting PA levels surpassing pre-pandemic baselines due to widespread adoption of hybrid exercise models. This recovery has fostered lasting changes toward hybrid exercise models, combining traditional and digital modalities, resulting in positive health outcomes across the cardiovascular, immune, metabolic, and psychological domains. Future public health strategies should emphasize flexible, diverse, and accessible exercise options, and further research should explore the sustainability and implications of these evolving exercise behaviors.